Concurrent chemoradiation therapy is associated with an accelerated risk of cardiovascular autonomic dysfunction in patients with nasopharyngeal carcinoma: A 9-year prospective follow-up study. (May 2022) - Huang, Chih-Cheng; Lai, Yun-Ru; Chiu, Wen-Chan; Fang, Fu-Min; Hsieh, Dong-Yi; Lien, Chia-Yi; Cheng, Ben-Chung; Chien, Chih-Yen; Huang, Tai-Lin; Kung, Chia-Te; Lu, Cheng-Hsien
Highlights: Cardiovascular autonomic dysfunction after CCRT is a progressive process. Cardiovagal impairment occurs in the early phase and persists in decline. Adrenergic dysfunction only showed significance after a nine-year follow-up. Both afferent and efferent baroreflex pathways can be involved after CCRT. Abstract: Background: Concurrent chemoradiation therapy (CCRT) is the mainstay treatment for patients with nasopharyngeal carcinoma (NPC). Baroreflex impairment can be a late sequela in patients after neck radiotherapy. We hypothesized that cardiovascular autonomic dysfunction is a progressive process that can begin after CCRT and persists for a longer period. Methods: Cardiovascular autonomic function was assessed in 29 newly diagnosed patients with NPC using standardized measures including heart rate response to deep breathing (HRDB), Valsalva ratio (VR), baroreflex sensitivity (BRS), and analyses of heart rate variability (HRV), biomarkers of oxidative stress, and inflammation at three different time points (baseline, immediately after CCRT, and 9 years after enrollment). A healthy control group was recruited for the comparison. Results: Although there was an aging effect on autonomic parameters in both groups during the 9 years of follow-up, the between-group comparison showed that there was a significant decrease in HRDB, VR, and HRV at the 9th year of follow-up in the NPC group. Repeated measures ANOVA after controlling for age and sex showed that both HRDB and triangle index of HRV had statistically significant differences between the two groups. Conclusion: Based on our results, cardiovascular autonomic dysfunction after CCRT is a progressive and dynamic process. Cardiovagal impairment occurs in the early phase and persists in decline, while adrenergic dysfunction is significant only after a 9-year follow-up. In contrast to the current opinion, our study showed that both afferent and efferent baroreflex pathways can be involved after CCRT.